Institutional determinants of ownership positions of foreign acquirers in Africa. (3rd September 2017) - Ellis, Kimberly M.; Lamont, Bruce T.; Holmes, R. Michael; Ro, Sangbum; Faifman, Leon; DeGhetto, Kaitlyn; Parola, Heather
Abstract : Research summary: Using unique features of the African context and blending institutional, hostage, and transaction cost theories, we address gaps in our understanding of institutional determinants of ownership position in cross‐border acquisitions (CBAs) in emerging countries. We focus on two traditional institutional determinants: Informal and formal institutional distances between the two firms' home countries and two determinants that are particularly acute in the African context: the colonial ties between and fractionalization of the two firms' home countries. We find colonial ties and uncertainty avoidance distance, an indicator of informal institutional distance, are negatively related to ownership position. Conversely, we show that formal institutional distance and the host country's fractionalization positively influence ownership levels, but the latter effect is weakened when acquirers come from more fractionalized home countries. Managerial summary: We examine the effects of four institutional factors that influence organizational decision‐making in the African context: (a) its colonial history, (b) differences in informal cultural norms, (c) differences in formal regulatory structures, and (d) ethnic and linguistic diversity within a country on the percentage of equity ownership that foreign acquirers hold in African target firms. Results indicate that this equity position is lower when colonial ties and greater differences in uncertainty avoidance exist between the acquirer's home country and the target African country. Conversely, foreign acquirers' equity ownership positions are higher when there are greater formal regulatory differences between the two countries and the host country is more ethnically and linguistically diverse, though the latter effect is reduced when the acquirer is from a home country that is also diverse.